IMPLEMENTASI PROGRAM SOSIALISASI ANTI BULLYING, EDUKASI PHBS DAN PEMERIKSAAN GRATIS DI DESA SUKOLILO - Naabigh Safety Lathifah; HALWA HALWA MUNAYA UMNUL AKIDAH; Septiana Amanda Melati Sukma; Muhammad Hilal; Zanuba Isna Aulia (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2026)
Background: Providing accessible health screening services combined with health education represents a crucial strategy for enhancing community wellness and disease prevention efforts. Geographic barriers, socioeconomic disparities, and insufficient healthcare infrastructure create significant obstacles to delivering adequate health services, especially within rural populations. A substantial portion of elderly individuals and community residents remain uninformed about their health status owing to infrequent medical check-ups and limited knowledge regarding disease prevention strategies. Purpose: To provide free health screening services, anti-bullying awareness activities, and education on Clean and Healthy Living Behavior (PHBS) to the community of Sukolilo Village in order to support early detection of non-communicable diseases and improve public health awareness. Method: The intervention utilized diverse educational approaches including interactive presentations, group discussions, and participatory question-answer sessions covering health maintenance, bullying prevention, and PHBS principles. Complimentary health assessments encompassed measurements of blood pressure, blood glucose levels, cholesterol, and uric acid concentrations. A total of 50 individuals participated, comprising general community members, senior citizens, and students from SDN 02 Sukolilo Elementary School. Results: The execution of complimentary health assessments and educational interventions in Sukolilo Village successfully enhanced community recognition regarding the significance of regular health monitoring and maintaining healthy lifestyles. Participants acquired valuable insights into early disease detection methods and PHBS implementation strategies. The anti-bullying awareness initiative effectively educated students about respecting diversity and fostering secure educational environments. Conclusion: This comprehensive program integrating complimentary health screenings, anti-bullying awareness, and PHBS education demonstrated significant effectiveness in advancing community health literacy and consciousness. The initiative underscores the critical importance of preventive and health promotion strategies within public health frameworks, particularly for communities experiencing limited healthcare facility access.